Fish counts and species at and around artificially introduced tetrapod fields in the southern North Sea, 2022 - Philipp Fischer; Miriam Lienkämper; Markus Brand (PANGAEA, 2025)
With increasing global change, coastal protection measures are becoming increasingly important for preserving our coastal features and infrastructure. Coastal protection often comes in the form of artificial structures however, artificial structures can also appear as renewable energy projects, maritime infrastructure and aquaculture installations. The ecological effects of such structures on the natural surroundings remains largely unclear. 36 tetrapod structures (4-footed concrete breakwaters each weighing 2.8 t) in groups of six were added to the MarGate underwater experimental area to the north of Helgoland, in the Southern North Sea, in 2009 at 5 and 10 m water depth. The 5 m fields TN5 (North), TM5 (Middle) and TS5 (South) have been monitored monthly, since their introduction, with respect to the abundance, species composition and size of the associated biota community. By carrying out this monitoring project, we aim to study the long-term effects of artificial structures on the local biotic community in shallow coastal ecosystems. Line transect based visual fish census conducted by trained scientific divers is used to survey the fish communities in the vicinity of each tetrapod field. For this, four 20m long line transects are laid out permanently in the four cardinal directions, each marked at 0, 5, 10, 15 and 20 m distance to the tetrapod field. Data collection is communicated by the diver via voice communication of the surface and noted directly in the standardized protocol together with metadata on algae coverage other environmental parameters.